2022
DOI: 10.1155/2022/1483101
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Environmental Enrichment Relieves Dysfunctional Cognition and Synaptic Protein Levels Induced by Prenatal Inflammation in Older CD-1 Mice

Abstract: A mounting body of evidence suggests that prenatal inflammation may enhance the rate of age-associated cognitive decline and may involve aberrant amounts of synaptic proteins in the hippocampus, including synaptotagmin-1 (Syt1) and activity-regulated cytoskeleton-associated protein (Arc). However, little is known about the specific impact of adolescent environmental enrichment (EE) on age-associated cognitive decline and the changes in synaptic proteins caused by prenatal inflammation. In this study, CD-1 mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 47 publications
2
19
0
Order By: Relevance
“…The results are in accordance with a previous report that upregulation of Syt-1 in the hippocampus has been found to cause neuron damage associated with prenatal stress-and hypothyroidism-induced cognitive impairment (Vara et al, 2002;Jia et al, 2010). Moreover, EE could improve MSD associated-cognitive deficits by reducing Syt-1 expression, which was consistent with our previous study that exposure to an EE from adolescence improved age-associated cognitive decline by downregulating the expression of Syt-1 (Zhang et al, 2022). The contradictory results regarding the relationship between Syt-1 expression level and cognitive function could be a result of differences in the specific mechanisms leading to cognitive impairment in different pathological models.…”
Section: Discussionsupporting
confidence: 93%
“…The results are in accordance with a previous report that upregulation of Syt-1 in the hippocampus has been found to cause neuron damage associated with prenatal stress-and hypothyroidism-induced cognitive impairment (Vara et al, 2002;Jia et al, 2010). Moreover, EE could improve MSD associated-cognitive deficits by reducing Syt-1 expression, which was consistent with our previous study that exposure to an EE from adolescence improved age-associated cognitive decline by downregulating the expression of Syt-1 (Zhang et al, 2022). The contradictory results regarding the relationship between Syt-1 expression level and cognitive function could be a result of differences in the specific mechanisms leading to cognitive impairment in different pathological models.…”
Section: Discussionsupporting
confidence: 93%
“…The offspring were reared up to adolescence (2-month-old) after birth (Spear, 2000 ; Kota et al, 2011 ; Zhang Z. Z. et al, 2022 ). Finally, a total of 16 mice, including 8 males and 8 females, were included in each group for behavioral analyses, western blotting, and RT-PCR experiments.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, studies based on MIA induced by daily i.p. LPS injections during G 15–17 showed that spatial learning and memory of pups were impaired until middle age [ 92 , 93 ], suggesting that embryonic inflammation may accelerate the cognitive impairment associated with brain aging. Mice about 8-weeks-old were exposed to EE from 2 months of age [ 92 ] or from weaning [ 93 ] until the end of the experiments, i.e., about 3 or 15 months of age.…”
Section: Beneficial Effects Of Exposure To Ee On Neuroinflammation In...mentioning
confidence: 99%
“…LPS injections during G 15–17 showed that spatial learning and memory of pups were impaired until middle age [ 92 , 93 ], suggesting that embryonic inflammation may accelerate the cognitive impairment associated with brain aging. Mice about 8-weeks-old were exposed to EE from 2 months of age [ 92 ] or from weaning [ 93 ] until the end of the experiments, i.e., about 3 or 15 months of age. EE alleviated deficits of hippocampal synaptic plasticity (hippocampal expression of the RNA-binding protein Staufen), memory performance, and anxiety symptoms caused by embryonic inflammation [ 92 ].…”
Section: Beneficial Effects Of Exposure To Ee On Neuroinflammation In...mentioning
confidence: 99%
See 1 more Smart Citation